2013
DOI: 10.1523/jneurosci.2290-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hap1–Tsc1 Interaction Regulates Neuronal mTORC1 Signaling and Morphogenesis in the Brain

Abstract: Tuberous sclerosis complex (TSC) is a leading genetic cause of autism. The TSC proteins Tsc1 and Tsc2 control the mTORC1 signaling pathway in diverse cells, but how the mTORC1 pathway is specifically regulated in neurons remains to be elucidated. Here, using an interaction proteomics approach in neural cells including neurons, we uncover the brain-enriched protein huntingtin-associated protein 1 (Hap1) as a novel functional partner of Tsc1. Knockdown of Hap1 promotes specification of supernumerary axons in pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Correspondingly, the Target Filter results suggested that PI3K/AKT/mTOR signaling may be altered via aberrant miRNA regulation of the tumor suppressor protein Tsc1 (table 5). The upregulation of miR-721 and subsequent downregulation of Tsc1 is significant with relevance to FASD-related abnormalities, given current evidence that knockdown of Tsc1 or its functional partner, huntingtin-associated protein 1 (Hap1) , profoundly impairs the positioning of pyramidal neurons in the hippocampus [79], leading to long-term neurological impairment including cognitive deficits and learning impairments [80]. These results argue that altered epigenetic mechanisms, including histone modifications and miRNA regulatory control, may reflect consequences of neurodevelopmental ethanol exposure that do not have a specific relationship to stress response but nonetheless exert long-term functional changes within the adult brain.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, the Target Filter results suggested that PI3K/AKT/mTOR signaling may be altered via aberrant miRNA regulation of the tumor suppressor protein Tsc1 (table 5). The upregulation of miR-721 and subsequent downregulation of Tsc1 is significant with relevance to FASD-related abnormalities, given current evidence that knockdown of Tsc1 or its functional partner, huntingtin-associated protein 1 (Hap1) , profoundly impairs the positioning of pyramidal neurons in the hippocampus [79], leading to long-term neurological impairment including cognitive deficits and learning impairments [80]. These results argue that altered epigenetic mechanisms, including histone modifications and miRNA regulatory control, may reflect consequences of neurodevelopmental ethanol exposure that do not have a specific relationship to stress response but nonetheless exert long-term functional changes within the adult brain.…”
Section: Discussionmentioning
confidence: 99%
“…To assess precise positions of ribosome occupancy on mRNAs, uniquely aligning reads with length between 25 and 35 nt were used. The unique reads were mapped to CDS coordinates using mapToTranscripts function from GenomicFeatures R package (Lawrence et al, 2013). The reads were assigned to the positions corresponding to the first nucleotide of the P-site, by shifting the 5Ј end of each read by ϩ12 (for reads 25-30 nt long), ϩ13 (31-34 nt) or ϩ14 (35 nt) positions.…”
Section: Methodsmentioning
confidence: 99%
“…CTSSs with at least four pyrimidines in the 5Јend 5 nt were identified as producing 5ЈTOP-like motif-containing mRNAs. For each dataset, total CTSS and 5ЈTOP-preceding CTSS were mapped within 500 bp to both directions of transcription start sites of canonical transcripts using GenomicAlignments' summarizeOverlaps function (Lawrence et al, 2013). The 5ЈTOP ratio was calculated as the division of 5ЈTOPpreceding CTSS count and total CTSS count for each gene and each dataset.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to collaboration with neuroscientists [20], we are working on Tuberous Sclerosis disease. When neuroscientists model Tuberous Sclerosis in 'in vitro' neuron culture, they observe bigger neuron soma than the control cells.…”
Section: Neurological Disease Applicationsmentioning
confidence: 99%